Perspektif Pengguna Terhadap Pemanfaatan Aplikasi Candil Sebagai Pendukung Layanan Perpustakaan Dispusipda - Rahma, Silkvi Kheir; Rusmana, Agus; Kusnandar, Kusnandar (Jurnal Pustaka Ilmiah, 2023)
The use of digital library applications is an easy way for users to get information. This study aims to-provide an overview of the user's perspective on the Candil application as a support for Dipusipda library services. In addition, this study aims to determine the accessibility and usability of the Candil application from the perspective and experience of users when using the Candil application. The method used is a qualitative method with a case study approach. Observation, interviews, and literature studies carried out data collection techniques. Observations are made by conducting research on Candil application features. Then there were ten informants who were interviewed who were active users of the Candil application through accidental sampling. This research results that the accessibility aspect of the Candil application fulfills information accessibility so that users can find information on the Candil application through the availability of easy and fast collections. Then the Candil application also fulfills the five existing usability aspects: Learnability, Efficiency, Memorability, Error, and Satisfaction.